The quality of life in anemic patients with chronic heart failure, depending on the presence or absence of chronic kidney disease - N. G. Ryndinа; P. G Kravchun; O. M. Shelest (Zaporožskij Medicinskij Žurnal)
Chronic heart failure is one of the most common and prognostically adverse disease of cardiovascular system. Presence of chronic heart failure is associated with poor quality of life. Quality of life in patients with chronic heart failure is largely determined by the presence of comorbidity. An important role is given to anemic syndrome, which is considered to be a marker of increased risk of death, quality of life disorders in patients with chronic heart failure.